Calculation of the blue water footprint in the pharmaceutical industry: Case of study for the production process of water for injections - Balaguera, Alejandra; López-de-Mesa, Daniel (Tecnología y ciencias del agua, 2026)
Society and industry contribute directly and indirectly to the depletion and contamination of water resources. The water footprint is an indicator that measures the total volume of freshwater consumption, and direct or indirect contamination by producers or consumers. The methodology for its evaluation includes three types of footprints: blue, green, and gray. The first two express the volume of water consumed according to the source (aquifers or groundwater for the blue, and rainwater for the green), and the third is the volume contaminated in the production process. This article focused on the calculation of the Water Footprint for the production process of Water for Injections (WFI), in Ecar laboratories in Medellín, Colombia. A comparison is made between the previous conventional distillation system and the new thermocompression system. Additionally, a sensitivity analysis based on the influence of variation of the production efficiency of the new system on the blue water footprint, is presented. As conclusions, it was found that thanks to the reduction of water waste, there was a decrease of 76 % in the water footprint of the new system compared to the previous one. Besides, a higher sensitivity of the water footprint was found when smaller efficiencies of the thermocompression method were considered, evidencing the importance of performing periodical maintenance on the production equipment.